Enrichment of imidacloprid and its metabolites in lizards and its toxic effects on gonads. (March 2020) - Yang, Lu; Shen, Qiuxuan; Zeng, Tao; Li, Jianzhong; Li, Wei; Wang, Yinghuan
Abstract: Soil contaminants can cause direct harm to lizards due to their regular swallowing of soil particles. As the world's fastest growing insecticide with long half-life in soil, the endocrine disrupting effect of neonicotinoids on lizards deserves more attention. In this report, we assessed the endocrine disrupting effect of imidacloprid on Eremias argus during 28 days of continuous exposure. Among the imidacloprid and its metabolites, only the metabolite 6-chloropyridic acid had a significant accumulation in the gonads and was positively correlated with its blood concentration. Imidacloprid might cause endocrine disrupting effects on lizards in two ways. First, the desnitro metabolites of imidacloprid could accumulate in the brain, inhibited the secretion of gonadotropin-releasing hormone, and ultimately affected the feedback regulation of hypothalamic-pituitary-gonadal related hormones. Secondly, imidacloprid severely inhibited the gene expression of the corresponding enzymes in the gonadal anti-oxidative stress system, causing histological damage to the gonads and ultimately affecting gonadal function. Specifically, exposure to imidacloprid resulted in abnormal arrangement of spermatogenic epithelial epithelium, hyperplasia of epididymal wall, and oligospermia of male lizard. Meanwhile, gene expressions of cyp17, cyp19, and hsd17β were severely inhibited in the imidacloprid exposure group, consistent with decreased levels of testosterone and estradiol in plasma. Imidacloprid exposure could cause insufficient androgen secretion and less spermatogenesis in male lizards. The risk of imidacloprid exposure to female lizards was not as severe as that of male lizards, but it still inhibited the expression of cyp19 in the ovaries and led to a decrease in the synthesis of estradiol. This study firstly reported the endocrine disruption of imidacloprid to lizards, providing new data for limiting the use of neonicotinoids. Graphical abstract: Image 1 Highlights: Blood exchange cause the accumulation of 6-chloropyridic acid in gonads. Desnitro metabolites of IMI affected the secretion of GnRH. IMI could cause oxidative stress damage to the gonads. IMI had a more serious impact on male lizards. Abstract : Imidacloprid could cause endocrine disrupting effects on lizards by affecting GnRH secretion and oxidative stress damage to the gonads.